Oxytocin, prostaglandin F2α, and scopolamine for uterine involution of dairy cows - Carbonari, Alice; Burgio, Matteo; Frattina, Lorenza; Ceci, Edmondo; Sciannamblo, Maurizio; Ricci, Pasquale; Cicirelli, Vincenzo; Rizzo, Annalisa (Frontiers in Veterinary Science, 2024)
The aim of the study was to compare the effect of three substances with ecbolic activity, Oxytocin, Prostaglandin F2α (PGF2α) and Scopolamine, on the uterine involution process in dairy cows and on the resumption of ovarian activity. Eighty bovine were randomly divided in four groups: GROUP C: 20 cows treated, within 24 hours of calving, with 5mL/head of saline solution; GROUP PG: 20 cows treated, within 24 hours of calving, with 150 µg/head of d-cloprostenol; GROUP OX: 20 cows treated, within 24 hours of calving, with 50 IU/head of oxytocin acetate; GROUP S: 20 cows treated, within 24 hours of calving, with 40 mg/q Scopolamine Butylbromide. Each cow was subjected to blood samples to evaluate the Hydroxyproline (HYP) levels, at T0, within 24 hours after calving, and T7, T14, T28, 7, 14 and 28 days after calving, respectively. At T14 and T28, an ultrasound examination was performed to measure the diameter of ex-pregnant horn. In all cows, the reproductive indices (days to first service and number of artificial insemination for conception) were evaluated. In all groups, the HYP concentrations have been rising from T0 to T28, with the maximum levels obtained at T28 in the groups PG and S. As regard the diameter of uterine horn, the comparison among the groups showed significant differences only at T28, with lower values in the group PG and S. In group S and PG, the days to first service were less than other groups. Treatment with Scopolamine and PGF2α resulted in better outcomes, evidenced clinically by more efficient uterine involution and faster ovarian recovery.